Application of struvite and / or struvite-based composite material in thermochemical energy storage
By using struvite and/or its matrix composite materials as thermochemical energy storage materials, the problems of poor circulation stability and low energy storage density of existing materials are solved, and efficient medium and low temperature thermal energy storage and regulation management are achieved.
Patent Information
- Application Number
- CN202311715115.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-13
- Publication Date
- 2025-03-21
AI Technical Summary
The existing medium and low temperature thermochemical energy storage materials have problems such as poor circulation stability, easy dehydration, corrosiveness and low energy storage density, which limits their widespread use in practical applications.
Strulotite and/or strulot-based composite materials are used as thermochemical energy storage materials, mineral synthesis is carried out through chemical reagents such as magnesium, potassium, phosphorus, sodium, ammonia salts and alkalis, or prepared by precipitation method and hydrated magnesium phosphate cement to form thermochemical energy storage materials with high energy storage density and good stability.
It realizes efficient storage and regulation management of medium and low temperature thermal energy, has the advantages of high heat storage density, non-degradation, non-corrosiveness, simple and diverse production methods, and is suitable for heat storage management needs in different fields.
Smart Images

Figure CN119662218A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of thermal energy storage, and in particular to the application of struvite and / or struvite-based composite materials in thermochemical energy storage. Background Art
[0002] Human survival and development are heavily dependent on the demand for energy. However, the current world energy structure is still dominated by traditional non-renewable energy such as oil, natural gas, and coal, supplemented by clean energy such as nuclear energy, solar energy, wind energy, and biomass energy. There are problems such as energy shortage, clean energy and technology yet to be developed. There is a lot of low-grade heat energy discharged into the environment in the form of waste heat in natural activities and human life and production activities. The temperature difference between it and room temperature ranges from a few degrees to tens of degrees, such as solar energy, geothermal energy, factory production waste heat, power plant waste heat, etc. The recycling and reuse of this type of heat energy can improve the comprehensive utilization rate of energy and alleviate the problem of energy shortage to a certain extent. Sensible heat storage, latent heat storage, and thermochemical energy storage are the three major energy storage methods at present. Among them, sensible heat storage stores energy by increasing or decreasing the temperature difference of the storage medium; latent heat storage stores energy by utilizing the storage medium to undergo physical state changes during the heat storage and release process; and thermochemical energy storage stores energy through endothermic or exothermic chemical reactions between components. Compared with sensible heat storage and latent heat storage, thermochemical energy storage has the advantages of higher energy storage density, lower heat loss, and long-term storage. However, due to its complex process technology and cyclic stability of energy storage materials, it is still in the research and demonstration stage.
[0003] Thermochemical energy storage materials are subdivided into thermochemical adsorption or absorption energy storage and thermochemical reaction energy storage according to the reaction type. Thermochemical adsorption / absorption energy storage is used for the storage of medium and low temperature heat sources, while thermochemical energy storage is used for the storage of high temperature heat sources. As medium and low temperature thermochemical adsorption energy storage materials, many inorganic salt monomer energy storage materials and inorganic salt / porous material composite materials have been developed in recent years, such as lithium chloride, calcium chloride, magnesium chloride, magnesium sulfate, zinc sulfate, strontium bromide, sodium sulfide, lanthanum chloride, lithium chloride / expanded graphite, strontium bromide / expanded graphite, calcium chloride / zeolite, magnesium chloride / zeolite, etc. However, the hydrated salt-based medium and low temperature chemical thermal storage materials of the authorized patent CN111978922B, such as magnesium sulfate heptahydrate, magnesium nitrate hexahydrate, sodium sulfide pentahydrate, etc., have problems such as poor cycle stability and insufficient hydration reaction; while the halogen-containing thermochemical energy storage materials such as magnesium chloride, calcium chloride, lithium chloride, lanthanum chloride, strontium bromide, lithium bromide, etc., although the cycle stability is relatively good, the energy storage density is relatively low, and it is very easy to lyse, resulting in leakage, corrosion of the reactor and other problems. Composite thermochemical energy storage materials with hydrated salt as the main body of energy storage functionality, such as the authorized patent CN110079280A and the applied patent CN115678511A, can solve the problems of heat loss, deliquescence, leakage and corrosion in the hydrated salt energy storage process to a certain extent. However, when preparing composite materials, there are problems such as high purity requirements for the matrix material, complicated manufacturing process and high production cost, which are not conducive to practical application.
[0004] In summary, for the recovery and reuse of medium-low-temperature and low-grade heat sources, it is urgent to develop new inorganic salt / hydrothermal chemical energy storage materials to overcome the common problems existing in the above-mentioned traditional inorganic salt / hydrothermal chemical energy storage materials and reduce the technical difficulties in the practical application of thermochemical energy storage materials. Summary of the invention
[0005] The purpose of the present invention is to provide an application of struvite and / or struvite-based composite materials in thermochemical energy storage in order to solve the above problems. It is a new type of inorganic salt / water thermochemical energy storage material and its storage, utilization or regulation and management of low-grade heat sources. Struvite and / or struvite-based composite materials are used as thermochemical energy storage materials. The thermochemical energy storage material has a high energy storage density and can realize effective storage and regulation and management of medium and low temperature thermal energy.
[0006] The purpose of the present invention is achieved through the following technical solutions:
[0007] The purpose of the present invention is to provide the use of struvite and / or struvite-based composite materials in thermochemical energy storage, characterized in that struvite and / or struvite-based composite materials are used as thermochemical energy storage materials.
[0008] Furthermore, the thermochemical energy storage material is used for storage and regulation management of medium and low temperature thermal energy.
[0009] Furthermore, the medium and low temperature thermal energy includes solar energy, geothermal energy, industrial waste heat, power plant waste heat, battery module heat, etc.
[0010] Furthermore, the struvite includes one or more of amino-struvite (MgNH4PO4·6H2O), potassium-struvite (MgKPO4·6H2O), sodium-struvite (MgNaPO4·7H2O), etc.
[0011] Furthermore, the struvite-based composite material includes one or more of a struvite / expanded graphite composite material, a struvite / vermiculite composite material, a struvite / zeolite composite material, a struvite / nanocarbon fiber composite material, a struvite / inorganic binder composite material, a struvite / organic binder composite material, and the like.
[0012] Furthermore, the struvite (struvite monomer) is obtained by synthesizing struvite minerals using chemical reagents such as magnesium, potassium, phosphorus, sodium, ammonium salts and alkali.
[0013] Furthermore, the struvite (struvite monomer) is obtained by precipitating magnesium in seawater.
[0014] Furthermore, the struvite (struvite monomer) is obtained by precipitating phosphorus in wastewater or sewage.
[0015] Furthermore, the struvite (struvite monomer) is obtained by hydrating magnesium phosphate cement.
[0016] Furthermore, the struvite-based composite material is prepared by compounding struvite with other functional materials, fillers, gels, and the like.
[0017] Furthermore, the struvite-based composite material has struvite as a functional component, and porous materials, high thermal conductivity materials, gels, etc. as other components.
[0018] Furthermore, the gel comprises an inorganic binder material and an organic binder material.
[0019] Furthermore, the struvite in the struvite-based composite material can be obtained through the above-mentioned preparation method.
[0020] Furthermore, the porous material in the struvite-based composite material includes expanded graphite, expanded vermiculite, zeolite, porous ceramsite, and the like.
[0021] Furthermore, the high thermal conductivity material in the struvite-based composite material includes carbon fiber, graphene, carbon powder, alumina powder, silicon carbide powder, etc.
[0022] Furthermore, the inorganic binder in the struvite-based composite material includes a phosphate binder, a silicate binder, and the like.
[0023] Furthermore, the organic binder in the struvite-based composite material includes natural binder, synthetic high-molecular binder, and the like.
[0024] Furthermore, the thermochemical energy storage material is used in a thermochemical energy storage reactor to store and regulate thermal energy. The thermochemical energy storage material can be directly applied to a thermochemical reaction bed or reactor to store and regulate thermal energy.
[0025] Furthermore, the thermochemical energy storage material is used to prepare a thermal energy storage plate or a thermal energy storage brick to store and regulate thermal energy. The thermochemical energy storage material can be further combined with an adhesive matrix to make a thermochemical energy storage plate or a block material to store and regulate thermal energy.
[0026] Furthermore, the thermochemical energy storage material is used in battery modules to delay thermal runaway and spread of the battery.
[0027] Furthermore, the struvite and / or struvite-based composite materials have the advantages of high heat storage density, moderate working temperature, non-deliquescent, non-corrosive, simple and diversified manufacturing methods, etc., and can meet the heat storage management needs in different fields.
[0028] The struvite is used as a thermochemical energy storage material, and the struvite-based composite material is used as a struvite-based composite thermochemical energy storage material.
[0029] Compared with the prior art, the beneficial effects of the present invention are embodied in the following aspects:
[0030] 1) The present invention provides the application of struvite and / or struvite-based composite materials in thermochemical energy storage. The struvite and / or struvite-based composite materials have an operating temperature range of above 50°C and belong to medium-low temperature thermochemical adsorption energy storage materials. They not only have a high energy storage density, but are also insoluble substances and do not have the easy deliquescent problem commonly found in traditional inorganic salt energy storage materials. In addition, struvite can inhibit metal corrosion and avoid the problem of corrosion of reactors in traditional water and salt thermochemical energy storage materials.
[0031] 2) The struvite and / or its composite material involved in the present invention can be prepared by various methods, with simple operation and low cost, and can be applied to the recovery and reuse of low-grade heat sources, providing a new material and method for thermochemical energy storage.
[0032] 3) The present invention provides the application of struvite and / or struvite-based composite materials in thermochemical energy storage. Compared with the common disadvantages of traditional hydrated metal salt thermochemical energy storage materials such as easy deliquesce, corrosiveness, and low heat storage density, the thermochemical energy storage material of the present invention has the advantages of higher heat storage density, moderate working temperature, no deliquesce, no corrosiveness, simple and diversified preparation methods, etc., which can meet the energy storage management needs in different fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 It is the XRD spectrum of the struvite and / or the struvite-based composite material of the present invention.
[0034] Figure 2 It is the endothermic curve of magnesium sulfate heptahydrate, struvite and / or struvite-based composite material of the present invention at a heating rate of 10° C. / min.
[0035] Figure 3 The exothermic curves of the dehydrated magnesium sulfate, struvite and the struvite-based composite thermochemical energy storage material of the present invention at 20° C. and a water-to-solid ratio of 1.5.
[0036] Figure 4 The present invention shows the apparent morphology of potassium-struvite and magnesium sulfate heptahydrate (MgSO4·7H2O) after 20 cycles of endothermic / exothermic cycles, wherein (a) the apparent morphology of potassium-struvite after 20 cycles of endothermic absorption, (b) the apparent morphology of potassium-struvite after 20 cycles of exothermic release, (c) the apparent morphology of magnesium sulfate heptahydrate after 20 cycles of endothermic absorption, and (d) the apparent morphology of magnesium sulfate heptahydrate after 20 cycles of exothermic release.
[0037] Figure 5 It is the thermal enthalpy (DSC) diagram of dehydrated potassium-struvite (DeKstr) after moisture absorption and recovery (i.e., after one storage-release cycle) at 20°C and relative humidity of 98%. DETAILED DESCRIPTION
[0038] The present invention is described in detail below in conjunction with specific embodiments, but is by no means intended to limit the present invention. Features such as preparation methods, materials, structures or composition ratios not explicitly described in this technical solution are considered to be common technical features disclosed in the prior art.
[0039] The present invention relates to a novel thermochemical energy storage material and its storage, regulation and utilization of thermal energy. The novel thermochemical energy storage material is struvite and its composite material, including (but not limited to) amino (NH4 + -), potassium (K + -) and sodium (Na +-) Struvite and struvite-based composite materials, etc. The novel thermochemical energy storage material of the present invention can be obtained by (but not limited to) the following methods: 1) using chemical reagents to synthesize struvite minerals; 2) using precipitation method to precipitate phosphorus in wastewater (sewage) to recover struvite; 3) obtaining struvite hydration products by hydrating magnesium phosphate cement; 4) composite struvite with other functional matrices or fillers to prepare struvite-based composite thermochemical energy storage materials. Specific application methods include (but not limited to): 1) applied to thermochemical energy storage reactors in storage / release systems to store, regulate and utilize thermal energy;
[0040] 2) Mix struvite or struvite-based composite materials with adhesives or press them into thermochemical energy storage plates (bricks) of different geometric shapes to store, regulate and utilize thermal energy; 3) Apply them to battery modules to delay thermal runaway and spread of batteries. Compared with the common shortcomings of traditional hydrated metal salt thermochemical energy storage materials such as easy deliquesce, corrosiveness, and low heat storage density, the new thermochemical energy storage material of the present invention has the advantages of higher heat storage density, moderate working temperature, no deliquesce, no corrosiveness, simple and diversified manufacturing methods, etc., which can meet the energy storage management needs in different fields.
[0041] Example 1
[0042] In this embodiment, the thermochemical energy storage material can be obtained by synthesizing struvite minerals using chemical reagents such as magnesium, potassium, phosphorus, sodium, ammonium salts and alkali, as follows:
[0043] A certain amount of magnesium chloride hexahydrate and potassium dihydrogen phosphate were weighed and dissolved in deionized water at a magnesium / phosphorus molar ratio of 0.29 and a water-solid ratio of 3.33, and the mixture was fully mixed. The pH value of the mixture was adjusted to 8 (or above) with potassium hydroxide solution. After standing at room temperature for 1 day, the mixture was filtered and dried to obtain the target potassium-struvite thermochemical energy storage material. In this embodiment, the prepared potassium-struvite (Kstr) phase is as follows Figure 1 As shown, the endothermic process is Figure 2 As shown, the exothermic process is Figure 3 After 20 cycles of heat absorption and release, the apparent morphology of potassium-struvite is as follows Figure 4 shown.
[0044] Example 2
[0045] In this embodiment, the thermochemical energy storage material can be obtained by synthesizing struvite minerals using chemical reagents such as magnesium, potassium, phosphorus, sodium, ammonium salts and alkali, as follows:
[0046] A certain amount of magnesium chloride hexahydrate and sodium dihydrogen phosphate were weighed and dissolved in deionized water at a magnesium / phosphorus molar ratio of 0.29 and a water-solid ratio of 3.33, and the mixture was fully mixed. The pH value of the mixture was adjusted to 11 with a sodium hydroxide solution. After standing at room temperature for 1 day, the mixture was filtered and dried to obtain the target sodium-struvite thermochemical energy storage material. In this embodiment, the sodium-struvite (Nastr) phase is as follows Figure 1 As shown, the endothermic process is Figure 2 As shown, the exothermic process is Figure 3 shown.
[0047] Example 3
[0048] In this embodiment, the thermochemical energy storage material can be obtained by synthesizing struvite minerals using chemical reagents such as magnesium, potassium, phosphorus, sodium, ammonium salts and alkali, as follows:
[0049] A certain amount of magnesium chloride hexahydrate and ammonium dihydrogen phosphate were weighed and dissolved in deionized water at a magnesium / phosphorus molar ratio of 0.29 and a water-solid ratio of 3.33, and the mixture was fully mixed. The pH value of the mixture was adjusted to 8 (or above) with ammonia water. After standing at room temperature for 1 day, the mixture was filtered and dried to obtain the target amino-struvite thermochemical energy storage material. In this embodiment, the amino-struvite (Astr) phase is as follows Figure 1 As shown, the endothermic process is Figure 2 As shown, the exothermic process is Figure 3 shown.
[0050] Example 4
[0051] In this embodiment, the thermochemical energy storage material can be obtained by synthesizing struvite minerals using chemical reagents such as magnesium, potassium, phosphorus, sodium, ammonium salts and alkali, as follows:
[0052] A certain amount of magnesium chloride hexahydrate and potassium dihydrogen phosphate were weighed and dissolved in simulated seawater at a magnesium / phosphorus molar ratio of 0.29 and a water-solid ratio of 3.33, and mixed thoroughly. The pH value of the mixture was adjusted to 8 (or above) with potassium hydroxide solution. After standing at room temperature for 1 day, the mixture was filtered and dried to obtain the target seawater to prepare potassium-struvite thermochemical energy storage material. The physical phase of seawater preparation of potassium-struvite (Kstr-SW) is as follows Figure 1 As shown, the endothermic process is Figure 2 As shown, the exothermic process is Figure 3 shown.
[0053] Example 5
[0054] In this embodiment, the thermochemical energy storage material can be obtained by precipitating magnesium in seawater, as follows:
[0055] A certain amount of magnesium chloride hexahydrate and potassium dihydrogen phosphate were weighed and dissolved in simulated wastewater at a magnesium / phosphorus molar ratio of 0.29 and a water-solid ratio of 3.33, and the mixture was fully mixed. The pH value of the mixture was adjusted to 8 (or above) with potassium hydroxide solution. After standing at room temperature for 1 day, it was filtered and dried to obtain the target wastewater to prepare potassium-struvite thermochemical energy storage material. Figure 1 As shown, the endothermic process is Figure 2 As shown, the exothermic process is Figure 3 shown.
[0056] Example 6
[0057] In this embodiment, the preparation method of the thermochemical energy storage material is as follows:
[0058] A certain amount of magnesium chloride hexahydrate and potassium dihydrogen phosphate were weighed and dissolved in deionized water at a magnesium / phosphorus molar ratio of 0.29 and a water-solid ratio of 3.33, and then potassium hydroxide solution was added to the mixture to adjust the pH to 8 (or above), and the mixture was left to stand at room temperature for 1 day, and finally filtered and dried to obtain the target potassium-struvite thermochemical energy storage material. The dehydrated potassium-struvite was placed in a constant temperature and humidity chamber (temperature 20°C, relative humidity 98%). The thermal enthalpy diagram (DSC curve) of the potassium-struvite after moisture absorption and recovery is as follows Figure 5 shown.
[0059] Example 7
[0060] In this embodiment, the thermochemical energy storage material can be prepared by compounding struvite with other functional materials, fillers, gels, etc., as follows:
[0061] The dead-burned magnesium oxide, potassium dihydrogen phosphate and water were mixed at a magnesium / phosphorus molar ratio of 4 / 1 and a water / solid ratio of 5 / 1 to prepare a suspension. After reacting for 1 day, the suspension was filtered and dried to obtain a struvite-based composite thermochemical energy storage material (S-Kstr). Figure 1 As shown, the endothermic process is Figure 2 As shown, the exothermic process is Figure 3 shown.
[0062] Example 8
[0063] In this embodiment, the thermochemical energy storage material can be prepared by compounding struvite with other functional materials, fillers, gels, etc., as follows:
[0064] The dead-burned magnesium oxide, potassium dihydrogen phosphate and water were mixed at a magnesium / phosphorus molar ratio of 4 / 1 and a water / solid ratio of 0.25 and injection molded into a struvite-based composite thermochemical energy storage plate (P-Kstr), the physical phase of which is as follows Figure 1 As shown, the endothermic process is Figure 2 As shown, the exothermic process is Figure 3 shown.
[0065] Example 9
[0066] In this embodiment, the preparation method of the thermochemical energy storage material is as follows:
[0067] A certain amount of magnesium chloride hexahydrate and potassium dihydrogen phosphate were weighed and dissolved in a 0.7wt.% expanded graphite suspension at a magnesium / phosphorus molar ratio of 0.29 and a water-solid ratio of 3.33, and then fully mixed. Potassium hydroxide solution was added to the mixture to adjust the pH to 8 (or above), and the mixture was allowed to stand at room temperature for 1 day. Finally, the target expanded graphite-potassium-struvite thermochemical energy storage material was obtained by filtration and drying. Expanded graphite-potassium-struvite (Kstr / EG) phase is as follows Figure 1 As shown, the exothermic process is Figure 3 shown.
[0068] Comparative Example 1
[0069] In order to verify the excellent heat storage performance of struvite and struvite-based composite thermochemical energy storage materials of the present invention, the traditional thermochemical energy storage material magnesium sulfate heptahydrate (MgSO4·7H2O) was selected as a reference. The endothermic process is shown in 2, and the exothermic process is shown in Figure 3 shown.
[0070] Comparative Example 2
[0071] In order to verify the good heat absorption / release cycle stability of the struvite and struvite-based composite materials of the present invention as thermochemical energy storage materials, the traditional thermochemical energy storage material magnesium sulfate heptahydrate (MgSO4·7H2O) was used as a reference. The apparent morphology of magnesium sulfate heptahydrate after 20 cycles of heat absorption-release is as follows Figure 4 shown.
[0072] pass Figure 1-5 The test results of the embodiments and comparative examples show that:
[0073] (1) The heat storage density of the potassium-struvite thermochemical energy storage material in Example 1 is 1003 J / g, which is 10% higher than that of magnesium sulfate heptahydrate 914 J / g in Comparative Example 1;
[0074] (2) The potassium-based-struvite thermochemical energy storage material in Example 1 has a cumulative heat release of 394 J / g in 0.5 h, which is 33% higher than the magnesium sulfate heptahydrate 297 J / g in Comparative Example 1;
[0075] (3) After 20 cycles of heat absorption and heat release, the magnesium sulfate heptahydrate in Comparative Example 2 was obviously liquefied after water absorption and heat storage, while the potassium-struvite in Example 1 had no obvious change in appearance, indicating good stability;
[0076] (4) The heat storage density of the sodium-struvite thermochemical energy storage material in Example 2 is 684 J / g, which is lower than that of magnesium sulfate heptahydrate in Comparative Example 1, but its heat storage density is still at a relatively high level;
[0077] (5) The cumulative heat release of the sodium-struvite thermochemical energy storage material in Example 2 is 72 J / g in 0.5 h, which is lower than that of magnesium sulfate heptahydrate in Comparative Example 1, but its heat storage density is still at a relatively high level;
[0078] (6) The thermal storage density of the ammonium-struvite thermochemical energy storage material in Example 3 is 1334 J / g, which is 46% higher than that of magnesium sulfate heptahydrate 914 J / g in Comparative Example 1;
[0079] (7) The cumulative heat release of the ammonium-struvite thermochemical energy storage material in Example 3 is 379 J / g in 0.5 h, which is 27% higher than that of magnesium sulfate heptahydrate 297 J / g in Comparative Example 1;
[0080] (8) The heat storage density of the potassium-based-struvite thermochemical energy storage material prepared by the seawater method in Example 4 is 1016 J / g, which is 11% higher than that of magnesium sulfate heptahydrate 914 J / g in Comparative Example 1;
[0081] (9) The cumulative heat release of the potassium-based struvite thermochemical energy storage material prepared by the seawater method in Example 4 is 412 J / g in 0.5 h, which is 39% higher than that of magnesium sulfate heptahydrate 297 J / g in Comparative Example 1;
[0082] (10) The heat storage density of the potassium-based-struvite thermochemical energy storage material prepared by the wastewater method in Example 5 is 1031 J / g, which is 13% higher than that of magnesium sulfate heptahydrate 914 J / g in Comparative Example 1;
[0083] (11) The cumulative heat release of the potassium-based-struvite thermochemical energy storage material prepared by the wastewater method in Example 5 is 412 J / g in 0.5 h, which is 39% higher than that of magnesium sulfate heptahydrate 297 J / g in Comparative Example 1;
[0084] (12) The thermal storage density of the potassium-based struvite after dehydration and moisture absorption recovery in Example 6 is 979.4 J / g, which is only 2.35% lower than the initial potassium-based struvite of 1003 J / g in Example 1, and is still 7.16% higher than the magnesium sulfate heptahydrate of 914 J / g in Comparative Example 1;
[0085] (13) The heat storage density of the potassium-struvite thermochemical energy storage material in the magnesium oxide and potassium dihydrogen phosphate suspension in Example 7 is 781 J / g, which is lower than that of magnesium sulfate heptahydrate in Comparative Example 1, but its heat storage density is still at a relatively high level;
[0086] (14) The potassium-struvite thermochemical energy storage material in the magnesium oxide and potassium dihydrogen phosphate suspension in Example 7 has a cumulative heat release of 231 J / g in 0.5 h, which is lower than the magnesium sulfate heptahydrate in Comparative Example 1, but its heat storage density is still at a relatively high level;
[0087] (15) The heat storage density of the potassium-struvite thermochemical energy storage material in the potassium magnesium phosphate cement in Example 8 is 692 J / g, which is lower than the magnesium sulfate heptahydrate in Comparative Example 1, but its heat storage density is still at a relatively high level;
[0088] (16) The potassium-based-struvite thermochemical energy storage material in the potassium magnesium phosphate cement in Example 8 has a cumulative heat release of 203 J / g in 0.5 h, which is lower than the magnesium sulfate heptahydrate in Comparative Example 1, but its heat storage density is still at a relatively high level;
[0089] (17) The heat storage density of the expanded graphite-potassium-struvite composite thermochemical energy storage material in Example 9 is 396 J / g for 0.5 h of cumulative heat release, which is 33% higher than the 297 J / g of magnesium sulfate heptahydrate in Comparative Example 1. In summary, the present invention provides a thermochemical energy storage method using struvite-based minerals as thermochemical energy storage materials. Compared with the traditional thermochemical energy storage method using hydrated salt thermochemical energy storage materials, the method involved in the present invention generally has the advantages of higher heat storage density, better cycle stability, and the raw material source can synergistically improve environmental friendliness.
[0090] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. Application of struvite and / or struvite-based composite materials in thermochemical energy storage, characterized in that: Use struvite and / or struvite-based composite materials as thermochemical energy storage materials.
2. The use of struvite and / or struvite-based composite materials in thermochemical energy storage according to claim 1, characterized in that: The struvite includes one or more of amino-struvite, potassium-struvite, and sodium-struvite.
3. The use of struvite and / or struvite-based composite materials in thermochemical energy storage according to claim 1, characterized in that: The struvite-based composite material includes one or more of a struvite / expanded graphite composite material, a struvite / vermiculite composite material, a struvite / zeolite composite material, a struvite / nanocarbon fiber composite material, a struvite / inorganic binder composite material, and a struvite / organic binder composite material.
4. The use of struvite and / or struvite-based composite materials in thermochemical energy storage according to claim 1, characterized in that: The struvite is obtained by synthesizing struvite minerals using chemical reagents.
5. The use of struvite and / or struvite-based composite materials in thermochemical energy storage according to claim 1, characterized in that: The struvite is obtained by precipitating magnesium in seawater or by precipitating phosphorus in wastewater or sewage.
6. The use of struvite and / or struvite-based composite materials in thermochemical energy storage according to claim 1, characterized in that: The struvite is obtained by hydrating magnesium phosphate cement.
7. The use of struvite and / or struvite-based composite materials in thermochemical energy storage according to claim 1, characterized in that: The struvite-based composite material is prepared by compounding struvite with other components.
8. The use of struvite and / or struvite-based composite materials in thermochemical energy storage according to claim 1, characterized in that: The thermochemical energy storage material is used in a thermochemical energy storage reactor.
9. The use of struvite and / or struvite-based composite materials in thermochemical energy storage according to claim 1, characterized in that: The thermochemical energy storage material is used to prepare a thermal energy storage plate or a thermal energy storage brick.
10. The use of struvite and / or struvite-based composite materials in thermochemical energy storage according to claim 1, characterized in that: The thermochemical energy storage material is used in a battery module.
Citation Information
Patent Citations
Composite heat storage material containing dihydrate salt
CN110079280A
Recycling technique of lithium iron phosphate production wastewater
CN104628206A
Method of desulfurizing flue gas by ammonia-magnesium combination and by-producing struvite
CN107789965A
Graphene aerogel thermochemical energy storage composite material regulated and controlled through pH value and temperature and preparation method of graphene aerogel thermochemical energy storage composite material
CN114106789A
Thermochemical adsorption composite heat storage material and preparation method thereof
CN116904168A